Experimental Research on Simulation Material for Water-Resisting Soil Layer in Mining Physical Simulation - Tao Yang; Jie Zhang (Advances in Materials Science and Engineering)
This paper focuses on the failure mechanism of a water-resisting soil layer with both coal excavation and seepage effect. Being taken the simulation principle of fluid-solid coupling as the research basis, we have established a new kind of experimental material for fluid-solid physical simulation (FPS). The material adopts river sand and clay as the aggregates, besides engine oil and low-temperature grease that are used as the gelatinizing agents. According to the relevant property testing on the experimental material, the mechanical parameters and seepage parameters of the material totally match the parameters of the soil layer, which satisfy requirements of the fluid-solid coupling experiment. Simultaneously, we have solved abundant material property problems, such as the material disintegration with water and visuality of water seepage in the simulation. Next, we have built up the FPS model to simulate coal excavation under water-bearing strata with the specific material. The results indicated that in the FPS, movement and failure mechanism of the water-resisting soil layer agree with the in-situ monitoring results. In addition, the revolution law of a mining-induced crack is also fitting the actual data. The mechanism of submarine seepage and its parameters on the material and the prototype are similar. All research results would be necessary for controlling mining-induced destroying of clay water-resisting property. Meanwhile, the model demonstrates that selection of the material and coupling parameters is valid. Finally, we can alter the material matching to obtain the layer materials with various characteristics, which would be applied in extensive experiments for studying soil layer failure and seepage simulation.